Design and Optimization of a Piezoelectric Stick-Slip Actuator with Distributed Compliance - Tingting Ye; Zhao Feng; Yangmin Li (Machines)
With increasing demand for high-precision motion control systems, high operational speed and load capacity are imposed with piezoelectric stick-slip actuators based on compliant mechanisms, yet their performances are often constrained by the step size and move speed. In this paper, a novel piezoelectric stick-slip actuator featuring flexure beams and a trapezoidal driving foot is proposed for high dynamic performance and load requirements. The trapezoidal structure consists of a trapezoidal driving foot to differentiate the friction in the stick and slip phases, four flexure beams for the high resonant frequency due to distributed compliance and the high load capacity due to structural geometry, and a rigid rod for motion transmission. At first, the mechanism design and the working principle are described in detail. Then, its dominant performances are predicted through finite element analysis, including the step size and the first natural frequency. On this basis, the structural parameters are optimized through the genetic algorithm. As a result, the forward displacement in the stick phase can be obtained as 4.8 <semantics>μ</semantics>m through FEA simulations, where the first natural frequency can be observed as 627 Hz.